Corporate education: Driving aspects towards networked corporate university - Silva Neves, Marta; de Sá Freire, Patricia (International Journal for Innovation Education and Research, 2021)
This article aims to analyze the maturity evolution process of the stages of the corporate education system, listing the driving aspects of this process. To accomplish it, a qualitative research with a descriptive exploratory approach was carried out through an integrative review. The survey and systematic review were based on the analysis of existing scientific knowledge about "corporate education" and "evolution of the corporate education system". In the end, it is possible to list 25 driving factors for the evolution of the corporate education system to be considered by organizations that intend to reach the last stage of evolution, the Networked Corporate University (NCU), the most contemporary model proposed by the literature. In conclusion, this study brings theoretical contributions advancing on the existing theories and practices, as it can be considered that, when the Corporate Education System evolves towards the NCU stage, it will meet the context requirement that drives it to amplify the vision, beyond human capital, to social and relational capital.